2020
DOI: 10.3389/fncel.2020.548376
|View full text |Cite
|
Sign up to set email alerts
|

Does Cholinergic Stimulation Affect the P2X7 Receptor-Mediated Dye Uptake in Mast Cells and Macrophages?

Abstract: Background: Extracellular ATP is a powerful trigger of neuroinflammation by activating immune cells via P2X7 receptors. Acetylcholine and nicotinic agonists inhibit ATP-triggered proinflammatory cytokines via the so-called "cholinergic anti-inflammatory pathway" (CAP). However, it remains unclear as to what stage of ATP-induced signaling cholinergic agents provide this anti-inflammatory effect. Using the specific property of P2X7 receptor to open a pathway permeable to large molecules, associated with activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 80 publications
(112 reference statements)
1
6
0
Order By: Relevance
“…Immune cells in the meninges are associated with the local meningeal lymphatic system [ 87 , 88 ] that provides a mechanism to clear metabolic waste from the brain and meninges themselves [ 89 ]. Consistent with the view that ATP, acting via P2X7 receptors, can trigger pro-inflammatory processes activating dural immune cells [ 27 , 83 , 84 ], we have observed that the P2X7-preferring agonist BzATP enhances release of the pro-inflammatory tumor necrosis factor-α (TNFα) and of the anti-inflammatory cytokine Il-10, both implicated in migraine pain [ 90 , 91 ]. Nevertheless, the release of these cytokines is similar in WT and KO mice lacking the meningeal lymphatic system [ 92 ].…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Immune cells in the meninges are associated with the local meningeal lymphatic system [ 87 , 88 ] that provides a mechanism to clear metabolic waste from the brain and meninges themselves [ 89 ]. Consistent with the view that ATP, acting via P2X7 receptors, can trigger pro-inflammatory processes activating dural immune cells [ 27 , 83 , 84 ], we have observed that the P2X7-preferring agonist BzATP enhances release of the pro-inflammatory tumor necrosis factor-α (TNFα) and of the anti-inflammatory cytokine Il-10, both implicated in migraine pain [ 90 , 91 ]. Nevertheless, the release of these cytokines is similar in WT and KO mice lacking the meningeal lymphatic system [ 92 ].…”
Section: Introductionsupporting
confidence: 86%
“…2 ). Notably, these mast cells could serve both as the target for ATP acting via P2X7 receptors [ 27 , 83 , 84 ] and as an additional source of ATP release [ 85 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…3 A–F). Notably, the P2X7 receptor is also expressed in the dural mast cells 48 , 49 . Stimulation with 100 µM BzATP significantly increased the levels of IL-10 (treatment effect: p < 0.001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular ATP, acting primarily via P2X7 receptors, is a powerful trigger of inflammatory reactions involving different dural immune cells, including mast cells 48 , 49 , 73 , 74 . Consistent with this view, we found that the stimulation of meninges with the P2X7 agonist BzATP enhanced the release of the pro-inflammatory TNFα and Il-10, which are both implicated in migraine pathology 75 , 76 .…”
Section: Discussionmentioning
confidence: 99%
“…The P2X7R is abundantly expressed on macrophages and exhibits a variety of functions in innate and adaptive immune responses. Numerous studies reveal that the sequelae of P2X7R activation on macrophages includes the generation of membrane currents [ 47 , 48 ], membrane permeabilization, uptake of large molecules [ 49 ], massive perturbations of Na + , K + , and Ca 2+ homeostasis [ 24 , 50 ], inflammasome activation, and interleukin processing [ 51 , 52 , 53 ]. Cell membrane blebbing [ 47 , 54 ] and spontaneous cell fusion [ 55 ] of macrophages are also mediated by P2X7Rs.…”
Section: The Regulation Of Pore Formation On Macrophages Via P2x7rsmentioning
confidence: 99%